“Look, ma, no hands!” Writing without typing: speech-recognition tools for future translators in the English language classroom - Martínez-Hernández, Ana-Isabel (2022)
Writing proficiency in a foreign language has been increasingly demanded in the workplace due to the value of multilingualism; thus, it cannot be neglected in the English classroom. ICTs have gained momentum in the development of competences in the target language as a motivational asset, not least writing skills. In that sense, this paper seeks to inspect the effects speech recognition tools have in terms of motivation and written production. This study was conducted at a Spanish university with 55 first-year Translation and Interpreting undergraduates who were surveyed about the applicability of the dictation tools available in Microsoft Word® and Google Docs® to compose a written text. Results suggest that, despite its limitations, speech recognition can prove useful for learners and can result in a motivational innovative strategy to engage them in the writing process.